Proteomic Strategies for Comprehensive Identification of Post-Translational Modifications of Cellular Proteins Including Low Abundant and Novel Modifications - Jeong, Jaeho; Lee, Jae-Jin; Lee, Kong-Joo (IntechOpen, 2012)
None